2020
DOI: 10.1016/j.tet.2019.130879
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed reactions of cyclopropanols, cyclobutanols and cyclobutenols

Abstract: The exploitation of the ring strain of cyclopropanols, cyclobutanols and cyclobutenols has led to a variety of Pd-catalyzed reactions, especially when the ring is substituted with other functions. Cross-coupling and domino reactions have also been reported. The present review gathers together the literature results with special attention to the procedures. Proposed mechanisms are described with, in some cases, personal comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 146 publications
0
15
0
Order By: Relevance
“…Cyclopropanols [72][73][74][75] and the CF 3 group [48][49][50][51][52] are of broad interest because of their important applications in synthetic and medicinal chemistry. Therefore, (trifluoromethyl)cyclopropanol is potentially valuable because it contains these two important functional groups.…”
Section: Synpacts Synlettmentioning
confidence: 99%
“…Cyclopropanols [72][73][74][75] and the CF 3 group [48][49][50][51][52] are of broad interest because of their important applications in synthetic and medicinal chemistry. Therefore, (trifluoromethyl)cyclopropanol is potentially valuable because it contains these two important functional groups.…”
Section: Synpacts Synlettmentioning
confidence: 99%
“… 31 37 For instance, they can participate in further intramolecular steps, or be cross-coupled with aryl-, 38 42 alkenyl-, 43 , 44 and alkynylhalides, 45 or propargylcarbonates, 46 among others. 29 , 47 , 48 Therefore, cyclopropyl- or cyclobutyl alcohols can behave as alkylating reagents under the appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel studies have demonstrated the ability of Pd to perform the opening of strained cycloalkanols through β-carbon elimination ( b , Scheme ). , This process leads to a σ-alkyl-Pd­(II) intermediate, which can evolve in different manners, depending on the substitution pattern of the cycloalkanol. For instance, they can participate in further intramolecular steps, or be cross-coupled with aryl-, alkenyl-, , and alkynylhalides, or propargylcarbonates, among others. ,, Therefore, cyclopropyl- or cyclobutyl alcohols can behave as alkylating reagents under the appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Three-membered cyclopropane motifs, a class of useful synthetic entities, are well-known applicable building blocks for C-C bond activation. [23][24][25] Since 2010, cyclopropanes, such as vinylcyclopropanes (VCPs) 26,27 and cyclopropanols, 28,29 have emerged as versatile synthons for C-H/C-C activation reactions. Generally, two different strategies based on the pathways of C-C cleavage in the catalytic system could be expected for the activation of cyclopropanes.…”
Section: Introductionmentioning
confidence: 99%